Nitretação por plasma do aço inoxidável ISO 5832-1 com fluxo intermitente de nitrogênio - Rubega Neto, Alfredo (2018)
Austenitic stainless steel is widely applied in industry due to its high resistance to corrosion and wearing. The thermochemical technique of nitriding by plasma at low temperatures focus to enhance wear resistance and hardness keeping its corrosion resistance high. The present work has the objective of evaluate the influence that the variation of nitrogen potential in the atmosphere for treatment on a Austenitic stainless steel ISO 5832-1 has on the properties of the material, such as, nitrided layer thickness, hardness and chromium nitride precipitation. The nitriding was performed at 430 ºC, with gas mixture of 50% of Ar, 25% of H2 and 25 of N2 and 4 hours of treatment time. The control of nitrogen potential was performed by doing pulsed flow discharges of nitrogen gas at predetermined times: 10/10, 5/15 and 2/18 where the numbers represents time in minutes that the gas remained on/off respectively. For comparison purposes continuous nitrogen flow discharge was also applied. Results has showed that for all pulse condition the thickness of the expanded austenite were >10 µm and there is a lower tendency to form CrN/CrN2 in the boundery grain and also for all the treatments, continuous and pulsed, it was observed the convergence of the nanohardness results what was not expected, therefor for further studies a more detailed evaluation of the nanohardness is necessary. This Article showed that there are a lot of potential on the use of nitrogen pulse in order to provide the control of the properties of the austenite expanded layer.